A systematic study of MOCVD reactor conditions and Ga memory effect on properties of thick InAl(Ga)N layers: a complete depth-resolved investigation. Issue 1 (4th December 2019) - Chauhan, Prerna; Hasenöhrl, S.; Vančo, Ľ.; Šiffalovič, P.; Dobročka, E.; Machajdík, D.; Rosová, A.; Gucmann, F.; Kováč, J.; Maťko, I.; Kuball, M.; Kuzmík, J.
Abstract : Thick InAlN layers (In-molar fraction >0.37) on GaN buffer layers were prepared using a close-coupled showerhead metalorganic chemical vapor deposition (MOCVD) reactor. Abstract : Thick InAlN layers (In-molar fraction >0.37) on GaN buffer layers were prepared using a close-coupled showerhead metalorganic chemical vapor deposition (MOCVD) reactor. This work provides a discussion of the dependence of reactor parameters (pressure, ammonia flow and temperature) and unintentional Ga-incorporation on structural, optical and chemical properties of those layers down to the nanoscale. Rutherford back-scattering spectrometry, Auger electron spectroscopy, and transmission electron microscopy with the energy dispersive X-ray analysis were used for in-depth chemical analysis of layers. A diminishing Ga-auto-incorporation in thick InAlN layer creates a chemically graded InAl(Ga)N interlayer that assists in releasing of interfacial strain and paves the way toward In-rich InAlN layer. The rate of unintentional Ga-auto-incorporation in InAlN layers increases with decreasing of growth temperature, and increasing of reactor pressure and ammonia flow during growth. Raman and photoluminescence spectroscopy were used to get the crystal structural fingerprint influenced by Ga-incorporation. We suggested that Ga could incorporate at nitrogen vacancies at high reactor pressures (≥200 mbar). Screw dislocations and/or N-vacancies in InAl(Ga)N layers may be energetically favorable sites for In-incorporation and lead to compositional fluctuation and local In-rich InAl(Ga)N phase.